The bipolar phenotype: behavioural and neurobiological characteristics - Yip, S; Sarah Winsland Yip (2012)
Background: Adolescence and young adulthood are particularly vulnerable periods for the development of mental health disorders, including bipolar disorder (BD). Mental health screening at universities could aid in the early identification of particularly at- risk individuals, with the long-term aim of providing early treatment interventions to improve clinical outcomes. However, further research into the identification of appropriate behavioral and biological markers for vulnerability to psychiatric disorders – as well as into the acceptability and efficacy of mental health screening - is warranted. Methods: Young adults were recruited via an already existing Internet-based mental health screening survey of undergraduate students at the University of Oxford. In Study 1, qualitative interviews of young adults with and without previous mental health problems were conducted to assess the acceptability and efficacy of mental health screening within a university setting. In Studies 2-5 we explored the hypotheses of altered emotional decision-making, reward processing and neurostructural integrity as behavioral and neurobiological markers for vulnerability to bipolar disorder via the study of young adults with a common bipolar phenotype (BPP) - some of whom meet diagnostic criteria for bipolar II or not-otherwise-specified disorder (BD II/NOS). To that end, we employed a diverse range of methodologies: alcohol challenge (Study 2); neuropsychological task performance (Study 3); functional magnetic resonance imaging (fMRI; Study 4); diffusion tensor imaging (DTI) and voxel-based morphometry (VBM; Study 5). Results: Findings from Study 1 suggest that young adults are willing to participate in mental health screening within a university setting, and that such screening may be used to offer subsequent treatment interventions. Taken together, findings from Studies 2 and 4 suggest a general blunted reward response among unmedicated young adults at increased risk for BD during euthymia, and additionally suggest pathophysiological similarities between BD and alcohol use disorders (AUDs) that may provide a causal link between the elevated co-occurrence rates of the two disorders. Finally, findings from Study 5 suggest widespread white matter microstructural alterations – which are likely to be neurodevelopmental in origin – among antipsychotic- and mood-stabilizer naïve young adults with BD II/NOS. Conclusions: These data support the hypothesis of neurodevelopmental alterations identifiable prior to significant clinical impairment among young adults at increased risk of – or already meeting DSM-IV criteria for – bipolar disorder. They also suggest that young adults in higher education are willing to participate in mental health screening. Future studies should aim to identify more specific markers for individual disorders such as BD.